Microcavity Silicon Photodetectors at 1.55 μm. (26th October 2010) - Casalino, M.; Coppola, G.; Gioffrè, M.; Iodice, M.; Moretti, L.; Rendina, I.; Sirleto, L.
Abstract : The design, the realization, and the characterization of silicon resonant cavity enhanced (RCE) photodetectors, working at 1.55  μ m, are reported. The photodetectors are constituted by a Fabry-Perot microcavity incorporating a Schottky diode. The working principle is based on the internal photoemission effect. We investigated two types of structures: top and back-illuminated. Concerning the top-illuminated photodetectors, a theoretical and numerical analysis has been provided and the device quantum efficiency has been calculated. Moreover, a comparison among three different photodetectors, having as Schottky metal: gold, silver, or copper, was proposed. Concerning the back-illuminated devices, two kinds of Cu/p-Si RCE photodetectors, having various bottom-mirror reflectivities, were realized and characterized. Device performances in terms of responsivity, free spectral range, and finesse were theoretically and experimentally calculated in order to prove an enhancement in efficiency due to the cavity effect. The back-illuminated device fabrication process is completely compatible with the standard silicon technology.